Abu Hanifah Thoughts on Ownership and Wealth Distribution: A Solution to Modern Socio-Economic Inequality - Yunita, Elza Nikma; Syakur, Ahmad (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This article examines Abu Hanifah's thoughts on ownership and distribution of wealth as a solution to modern socio-economic inequality. The scope of the study includes a conceptual analysis of Abu Hanifah's views on property rights in Islam, the mechanism of wealth distribution, and its relevance in the context of contemporary economics. The purpose of this study is to explore the values ​​of distributive justice in classical Islamic thought and relate them to the challenges of global inequality today. The study uses a qualitative-descriptive method through a literature study of the works of Hanafi fiqh and contemporary Islamic economic literature. The results of the study show that Abu Hanifah places ownership as a social mandate that must be distributed fairly through zakat, sedekah, and waqf. His thoughts offer an alternative to the exploitative capitalist model and socialism that eliminates property rights. The conclusion of this study confirms that the concept of wealth distribution according to Abu Hanifah has philosophical and applicative value in building a just and sustainable economic system.